2018
DOI: 10.1103/physrevb.97.085414
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Raman scattering in dielectric nanostructures with electric and magnetic Mie resonances

Abstract: Resonantly enhanced Raman scattering in dielectric nanostructures has been recently proven to be an efficient tool for developing nanothermometry and experimental determination of their modecomposition. In this paper, we develop a rigorous analytical theory based on the Green's function approach to calculate the Raman emission from crystalline high-index dielectric nanoparticles. As an example, we consider silicon nanoparticles which have a strong Raman response due to active optical phonon modes. We relate en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…The model also revealed that the crystallization dynamics can give rise to secondary antennas embedded into the primary nanostructures, which broadens the horizons of light harvesting and thermal management at the nanoscale. This approach can be extended to many different materials and thermally-activated processes, including laser resonant printing (28), diffusion-based doping of semiconductors, nanofabrication of all-dielectric and hybrid devices for enhanced vibrational spectroscopy (29)(30)(31) and photothermal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The model also revealed that the crystallization dynamics can give rise to secondary antennas embedded into the primary nanostructures, which broadens the horizons of light harvesting and thermal management at the nanoscale. This approach can be extended to many different materials and thermally-activated processes, including laser resonant printing (28), diffusion-based doping of semiconductors, nanofabrication of all-dielectric and hybrid devices for enhanced vibrational spectroscopy (29)(30)(31) and photothermal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show how far-field Raman spectroscopy -a technique primarily known for sensing [5] -can be used as a versatile characterization tool for high-refractive-index nanostructures. Raman spectroscopy measures inelastic scattering of photons from phonon and vibrational modes in materials and its signal strength depends dramatically on the electric near-field enhancement [6,7,8]. This dependency has driven research in surface-enhanced Raman spectroscopy to create surfaces that amplify the local electric field outside nanostructures for sensing of nearby molecules [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of Raman scattering is amplified by the internal near-field enhancement produced by Mie resonances in silicon nanoparticles [7,8,22]. This has been exploited for detecting these resonances, but also for other applications such as thermometry, crystallinity characterization and nonlinear spectroscopy [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown through numerical simulations and also experimental validation that dimer structures made of high refractive index materials produce both electric and magnetic hotspots in infrared 11 and in the visible spectral range 8,12 . The enhancement is produced by the displacement currents and the electric and magnetic dipole-dipole interactions in the dielectric dimers 11,13 . Dielectric dimers not only enhance the field, but they also provide control over the directivity of the far field radiation of the emitters, without quenching the nearby emitters and lowering their quantum efficiency 8 .…”
Section: Introductionmentioning
confidence: 99%